Frequency effects in silane plasmas for plasma enhanced chemical vapor deposition - Howling, A. A.; Dorier, J. L.; Hollenstein, C.; Kroll, U.; Finger, F. (My University, 1992)
It is now generally recognized that the excitation frequency is an important parameter in radio-frequency (rf) plasma-assisted deposition. Very-high-frequency (VHF) silane plasmas (50–100 MHz) have been shown to produce high quality amorphous silicon films up to 20 Å/s [H. Curtins, N. Wyrsch, M. Favre, and A. V. Shah, Plasma Chem. Plasma Processing 7, 267 (1987)], and therefore the aim of this work is to compare the VHF range with the 13.56 MHz industrial frequency in the same reactor. The principal diagnostics used are electrical measurements and a charge coupled device camera for spatially resolved plasma-induced emission with Abel inversion of the plasma image. We present a comparative study of key discharge parameters such as deposition rates, plasma uniformity, ion impact energy, power transfer efficiency, and powder formation for the rf range 13–70 MHz.